The 'club' cell and behavioural and physiological responses to chemical alarm cues in the Nile tilapia - Barreto, Rodrigo Egydio [UNESP]; Barbosa Junior, Augusto; Casari Giassi, Ana Catarina; Hoffmann, Anette (Taylor & Francis Ltd, 2010)
The alarm response to skin extract has been well documented in fish. In response to skin extract, there is a decline in both locomotion activity and aggressive interactions. Our observation herein of these responses in the cichlid Nile tilapia, Oreochromis niloticus, confirmed the existence of the alarm response in this species. However, so far there has been a paucity of information on the autonomic correlates of this response. In this study, the ventilatory change in response to the chemical alarm cue was evaluated. This parameter was measured 4 min before and 4 min after exposure to 1 mL of either conspecific skin extract or distilled water (extract vehicle). Skin extract induced an increase in the ventilation rate, which suggested an anticipatory adjustment to potentially harmful stimuli. The chemical cue (alarm substance) also interfered with the prioritisation of responses to different environmental stimuli (stimuli filtering); this was suggested by the observation that the Nile tilapia declined to fight after exposure to a cue that indicates a risk of predation. Furthermore, histological analysis of the Nile tilapia skin revealed the presence of putative alarm substance-producing (club) cells.
Keywords: Nile tilapia; anti-predator behaviour; alarm response; chemical communication; ventilatory response